Strategi Komunikasi Pendidikan Berbasis Generative AI dalam Membangun Pembelajaran di Perguruan Tinggi - Rusli Akhmad Junaedi (UPT Publikasi Ilmiah UNISBA, 2025)
This study aims to explore educational communication strategies based on Generative AI (GenAI) in building innovative learning in higher education. This study is motivated by the fact that the development of artificial intelligence (AI) technology, especially Generative AI (GenAI), has had significant impacts on various sectors, including higher education. Still, while GenAI offers many opportunities to improve learning effectiveness, some challenges need to be overcome, such as the risk of plagiarism and dependence on technology. Qualitative research was the methodology used, with data triangulation used for analysis after data collection methods such as observation, interviews, and note-taking were employed. The findings from this study are that GenAI-based educational communication strategies have the potential to improve the quality of learning, personalization, and interaction between students and teachers. However, challenges such as plagiarism and the need for digital literacy must be addressed. GenAI can be an effective tool in creating an innovative and engaging learning environment. Institutions should develop clear guidelines on the use of GenAI, ensure proper use, and prevent plagiarism. Teachers and students should engage in digital literacy training to understand GenAI and integrate it into the learning process.